Triple bottom line aspects and sustainable supply chain resilience: A structural equation modelling approach - Tundys, Blanka; Wiśniewski, Tomasz (Frontiers in Environmental Science, 2023)
The purpose of this paper is to investigate which of sustainability elements, in the context of triple bottom line (TBL), are used to build sustainable supply chain resilience. This paper presents a new body of knowledge and contribution to the literature by relating the triple bottom line (TBL) context to the building of sustainable supply chain resilience using structural equation modelling. The research were used to understand that individual sustainability factors matter and play a role in the context of supply chain resilience. A survey questionnaire was designed to collect this data from the research respondents. To statistical analysis was first Confirmatory Factor Analysis (CFA) conducted and used, then for the analysis and interpretation structural equation model. The findings indicate that individual sustainability factors matter and play a role in the context of supply chain resilience. A number of previous studies have developed broad catalogues of sustainability factors influencing supply chains, however, to date no convincing evidence has been presented as to which of the range of elements identified, and how they influence supply chain resilience building. Despite the large number of publications on sustainable supply chain and resilience building, there is still a gap and lack of proper consideration of TBL-related criteria as elements that can determine mechanisms for building supply chain resilience in the context of sustainable development. This paper operationalizes a using the structural research model to using a structural research model to investigate how and in which relationships the different elements of the triple bottom line influence the resilience of supply chains.